Mitigating Construction Waste Pollution for Environmental Sustainability: An Integrated Approach: Mitigasi Pencemaran Limbah Konstruksi untuk Kelestarian Lingkungan: Pendekatan Terintegrasi - Zaenal Aulil Fauzany; Muhammad Alvan Rizki; Atik Wahyuni; Budwi Harsono (Academia Open, 2023)
This scientific article addresses the pressing issue of environmental pollution arising from construction waste, particularly its adverse effects on water quality due to rapid urban development with insufficient environmental considerations. Employing a multidisciplinary approach encompassing literature review and legal analysis, this study investigates the detrimental impacts of construction waste pollution on human health, economic losses, and disruptions to natural ecosystems. The research underscores the critical need for enhanced awareness and action among government entities, contractors, and the public to safeguard the environment from the deleterious effects of construction waste pollution, thereby preserving natural ecosystems and upholding environmental standards. The study's findings emphasize the imperative role of governments in promoting environmental management and regulation, emphasizing the urgency of concerted efforts to address this global environmental challenge. Highlights: Construction waste pollution poses a significant threat to water quality and the environment, especially in rapidly urbanizing areas with inadequate environmental planning. This study employs a multidisciplinary approach, including literature review and legal analysis, to assess the adverse impacts of construction waste on human health, economics, and natural ecosystems. The research underscores the urgency of raising awareness and taking action, involving government bodies, contractors, and the public, to protect the environment, preserve natural ecosystems, and uphold environmental standards. Keywords: Construction Waste Pollution, Water Quality, Environmental Considerations, Multidisciplinary Approach, Environmental Management